Flowering Phenology and Morphological Characterization of Butterfly Pea (Clitoria ternatea L.) - Miranda Tiara Putri; Pinta Murni; M. Erick Sanjaya (Postgraduate, University of Mataram, 2026)
Butterfly pea (Clitoria ternatea L.) is one of the plants that has potential as a medicinal plant. This potential is based on the many compounds that can be useful in the pharmacological field. Information on flowering phenology and morphological characterization of Butterfly pea flowers is the focus of this study. This study aims to examine each phase that occurs during the stages of flower development associated with environmental factors, and identify the morphological characteristics of butterfly pea flowers. This research was conducted at Ternate Street, The Hok, Jambi Province, in July-September 2024. The data generated are descriptive, qualitative, and quantitative. The results showed that butterfly pea flowers have a flowering stage that lasts for 11-14 days, with environmental factors that tend to be unstable. Morphological characterization of butterfly pea shows that flowers include papilionaceous, namely flowers with irregular corolla arrangement with a total of five strands and including hermaphroditus flowers with zygomorphus type and there are two bractea organs.